THE EDUCATIONAL ROLE OF SCHOOL IN SPORT DEVELOPMENT AND HEALTH PROMOTION IN SUBURBAN AREAS - CASE STUDY - Szabó, Sándor; Szabó, Nándor Zsolt (Stadium - Hungarian Journal of Sport Sciences, 2024)
This study investigates the sports preferences and participation levels among young residents of Soroksár, a district on the outskirts of Budapest, Hungary. Utilizing a mixed-method approach, data was collected through a questionnaire survey conducted in autumn 2023. Statistical analysis was performed to assess the significance of factors influencing sports participation. The results indicate that local infrastructure and accessibility significantly impact sports engagement among youth, with preferences leaning towards sports readily available in the community. Notably, early initiation of sports participation positively correlated with academic achievement, emphasizing the importance of holistic development through sports. The findings underscore the need for comprehensive infrastructural development to support mass sports participation and promote healthy lifestyles. Local policymakers are urged to prioritize investments in sports facilities and opportunities, recognizing the multifaceted benefits of sustained sports engagement beyond elite-level support. This study provides insights into sports participation in Soroksár and calls for further research to inform evidence-based interventions promoting physical activity and intellectual development among youth.